PENGARUH PERTUMBUHAN EKONOMI, INDEKS PEMBANGUNAN MANUSIA DAN BELANJA LANGSUNG TERHADAP KEMISKINAN KABUPATEN/KOTA DI PROVINSI JAMBI - Muhammad Amali (Universitas Batanghari Jambi, 2017)
The data in the research is the secondary data with quantitative method namely, the total of poverty resident, economic growth, shopping data regency/city in Jambi province in 2010-2013 by using panel data. The result of research indicated that as parcial economic growth (PER) and index human building (IPM) influence positive regarding poverty (Y) while direct shopping (BL) influence positive regarding poverty (Y). this thing look like claimed statistic –t value for variable PER (B1) which the value bigger from t-prob (-2,267347>0,0288), it means H0 refused H1 accepted. This thing indicated that economic growth (PER) as long period 2010-2013 influenced significant regarding poverty regency / city in Jambi province. For statistic –t value for variable index human building IPM (B2) claimed the value which bigger from T-prob (1,490156<0,1440), it means H0 accepted H1 refused. This indicated that IPM influence nothing significant regarding development or rising poverty regency / city in Jambi province. However, as simultaneous for economic growth (PER) and index human building (IPM) and direct shopping (BL) influence significant poverty development (Y) regency/city in Jambi province. Keyword : total resident poverty, economic growth, direct shopping data and data indeks human building